ANALYZING STUDENT INTERPERSONAL INTELLIGENCE BASED ON GENDER IN ELEMENTARY SCHOOL - Masyithoh, Siti; Muthmainah, Hafsah; Ratnaningsih, Sita (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Kediri, 2023)
This study aims to determine and describe the differences in interpersonal intelligence between male and female students in the high class of Sahabat Alam Elementary School. This research was conducted in the even semester of the 2021/2022 academic year. The method used in this research is a descriptive quantitative method using data collection techniques in the form of survey methods. The sample in this study consisted of a high class totaling 66 students. Data was collected using an instrument in the form of an Interpersonal Intelligence questionnaire with a Likert scale model containing 13 items with a valid value (rtabel = 0,27). Data analysis used an Independent Sample t-test. The results of this study indicate differences in students' Interpersonal Intelligence based on gender. The results showed that female students obtained an average of higher interpersonal intelligence than the average value of male students' interpersonal intelligence. It can be seen from the t-test results of the interpersonal intelligence of female and male students of -4.208 with a significance level of 0.05. Thus, this shows differences in the interpersonal intelligence of male and female students in elementary schools.